The Gilles De La Tourette Syndrome-Quality of Life Scale for Children and Adolescents (C&A-GTS-QOL): Development and Validation of the Italian Version - Andrea E. Cavanna; Chiara Luoni; Claudia Selvini; Rosanna Blangiardo; Clare M. Eddy; Paola R. Silvestri; Paola V. Calì; Stefano Seri; Umberto Balottin; Francesco Cardona; Renata Rizzo; Cristiano Termine (Behavioural Neurology)
Background: Gilles de la Tourette syndrome (GTS) is a chronic childhood-onset neuropsychiatric disorder with a significant impact on patients’ health-related quality of life (HR-QOL). Cavanna et al. (Neurology 2008; 71: 1410–1416) developed and validated the first disease-specific HR-QOL assessment tool for adults with GTS (Gilles de la Tourette Syndrome-Quality of Life Scale, GTS-QOL). This paper presents the translation, adaptation and validation of the GTS-QOL for young Italian patients with GTS.